Surgical Outcome of Dacrystorhinostomy in Fistulous Dacryocystitis: Doi: 10.36351/pjo.v37i4.1265 - Ahmed, Noman; Shaikh, Arsalan Ahmed; Ahmed, Munawar; Narsani, Ashok Kumar; Ali Bahoo, Muhammad Luqman (Pakistan Journal of Ophthalmology, 2021)
Purpose: To study the surgical outcomes of Dacryocystorhinostomy (DCR) in fistulous dacryocystitis. Study Design: Quasi Experimental study. Place and Duration of Study: The detailed study was carried out in the Institute of Ophthalmology, Liaquat University Hospital Jamshoro, between September 2018 to August 2020. Material and Methods: We analyzed the histories of 30 patients taking the DCR procedure and noted their mean age, standard deviation, follow-up time, complications and other details. We also reported the intraoperative anatomical results, postoperative analysis, and variable groups vs. outcomes post-surgery using SPSS Version 20. Results: The mean patient’s age was 44.2 ± 4.13years, where males to female percentages were 27% to 73%. We noted significant changes in patients with a success rate of 87% displayed by no relieved epiphora and lacrimal patency in 1 month, 3 months, and 6 months. The mean time of the patients was 4 months varying between 1 to 8 (months) and the variable group values vs. surgical outcomes showed no significant association between the variables (p-value ranging from 0.195 to 0.935). Conclusion: Complications resulting in some patient’s post-surgery are manageable and the surgical technique has a good success rate. Key Words: (DCR) Dacryocystorhinostomy, lacrimal Patency, fistulous Dacryocystitis, Scarring.